Using an Ounce of Prevention - Does It Reduce Health Care Expenditures and Rea; Pound of Profits: A Study of the Financial Impact of Wellness and Health Risk Screening Programs. - Phillips, Janet (2008)
Keywords: dept.acc; faculty_collection; sabbatical_report

Struggling for - Profit Hospitals Sink Further After Sale to Not-for-Profit Owners. - Phillips, Janet (Spring;Accounting., 2000)
Keywords: dept.acc; faculty_collection; sabbatical_report

Improving Student Performance in Introductory Accounting - Raising Minimum Grade Standards is Not the Answer - Phillips, Janet (The Accounting Educators' Journal, 2021)
An ongoing debate continues at universities surrounding whether or not to raise minimum grade standards. Because of an inherent risk that enrollments may decline as a result, it is important to examine whether minimum grade policies are associated with improved student performance. To address this issue, the current study examines the relationship between higher minimum grade requirements in introductory accounting and student grades. The new minimum grade requirement of â€œCâ€ was established beginning with the fall 2015 semester for introductory accounting to strengthen the quality of the program for an AACSB application. The research design included modeling introductory accounting grades over a ten-year period to examine any effect of the increase in the minimum grade on studentsâ€™ grades in the course. The multivariate regression equation considered variables previously found associated with introductory accounting grades (i.e., status as accounting major, grade point average, mathematics preparedness and previous experience taking the course). An additional dichotomous variable was introduced to capture the impact of students on the new program. All students were taught by the same professor, using the same textbook, teaching philosophy and examination format to enhance the comparison. Results suggest average grades in introductory accounting did not improve as expected.
Keywords: dept.acc; peer-reviewed; ⛔ No DOI found

Using an ounce of prevention: does it reduce health care expenditures and reap pounds of profits? A study of the financial impact of wellness and health risk screening programs. - Phillips, Janet F (Journal of health care finance, 2009)
As we are all well aware, health care expenditures in the United States are out of control and growing at epic proportions. Since private industry shoulders a significant burden of paying these rising health care costs, the huge and ever increasing sum paid by these corporations continues to impact the US economy translating into higher prices of services and manufactured goods and reduced job opportunities when companies outsource jobs or locate manufacturing facilities to avoid paying health care benefits for workers. As a result, health care expenditures have become a centerpiece of an enormous public policy debate as Congress is currently working on several versions of a bill to completely revise health care from the ground up. This research project was accomplished to examine the effectiveness of one approach to control rising health care costs and contain corporate financial responsibility--the establishment of wellness and health risk screening programs to improve the health of employees. Total health care cost per insured individual was gathered through an online survey directly from health care benefit administrators. The survey also asked information about wellness and health risk screening programs and the related responses were used to determine if there were a relationship between health care costs and health prevention programs. While statistical analysis was hampered in the current study because of the small sample size, some valid conclusions were reached. The study was successful in identifying a benchmark of Average Total Health Care Cost per Individual from $5,100 to $5,800 for 2005 through 2007. This is especially interesting in light of the fact that an average of $7,026 was spent on health care per person in 2006 in the United States. The study was also able to contribute an estimate of the increase realized in these expenditures of 6 percent in 2007 over 2006, and 4 percent in 2006 over 2005, which were in fact similar to the national average. The final contribution of the study is to suggest an explanation for the costs which appear to be holding their own in terms of the national average. While this cannot be statistically verified, it does seem that the active participation of these companies in wellness programs could be a factor. Wellness programs were very popular in this sample of companies as 82 percent of the respondents answered "YES" when asked if the company funds their own employee wellness program. This is an impressive number of companies that have recognized wellness programs as a potential means to reduce employee health care costs. In regards to specific programs, at least 50 percent of respondents answered that they have smoking cessation, employee fitness, counseling, health risk screening, and bio-metric screening programs. The existence of health screening variables show an impressive 73 percent of respondents do practice some sort of health care screening, 50 percent offer biometric screening while 18 percent have onsite clinics and 23 percent run annual employee fairs.
Keywords: *Health Care Costs/td [Trends]; *Health Expenditures; *Health Promotion/ec [Economics]; *Occupational Health Services/ec [Economics]; Cost-Benefit Analysis; Health Care Costs; Health Expenditures; Health Promotion; Health risk screening program; Humans; Mass Screening; Mass Screening/ec [Economics]; Occupational Health Services; Preventative health programs; Risk Assessment; Risk Assessment/ec [Economics]; United States; Wellness program; article; biometry; dept.acc; employee; financial management; fitness; funding; government; health care cost; health care financing; health care industry; health care policy; health hazard; occupational health service; patient counseling; preventive health service; profit; responsibility; risk assessment; smoking cessation; wellbeing; ⛔ No DOI found

An Examination of the Relationship Between the Funded Status of Defined Benefit Pension Plans and the Financial Condition of Sponsoring Organizations – Public Vs Private Sector - Phillips, Janet F. (Journal of Accounting Ethics and Public Policy, 2022)
Defined benefit pension plans are a bedrock of the U.S. economy providing guaranteed payment streams at pre-established amounts. Results suggest public plans, sponsored by State and Local governments, and private plans, sponsored by public corporations, are unfunded. State plans were found to have the largest pension and unfunded pension liabilities. Examination of relationships between unfunded pension liabilities and fiscal or financial stability of sponsoring organizations suggests unfunded State pension plans are more likely to be sponsored by financially struggling sponsors measured by general obligation bond ratings. Local governments and Corporations with unfunded pension plans are less likely to be struggling financially. Fiscal distress of Local governments was measured by survival analysis. Corporation financial distress was quantified by a model designed to predict bankruptcy. Financially stable organizations failing to fund pension plans, in this case local governments and corporations, suggests a lack of social responsibility.
Keywords: Defined benefit pension plans; dept.acc; financial or fiscal distress; peer-reviewed; social responsibility; unfunded pension liabilities; ⛔ No DOI found

Accounting Majors Finish First – Results of a Five-Year Study of Performance in Introductory Accounting - Phillips, Janet F. (The Accounting Educators' Journal, 2015)
Delivery of a quality introductory accounting course is essential for schools of business. The first step in revitalization and improvement of the course is to identify factors suggested to be empirically related to succeessful completion. Accounting major status is of particular interest. While it has long been anecdotally observed and logically expected that accounting majors would earn higher grades in introductory accounting, it is rarely addressed in empirical studies. To investigate the impact of accounting major status on performance in introductory accounting, a sample of 398 students exposed to the same professor, text, teaching and examination format over five-years was gathered. Results suggest accounting major status was in fact a significant positive predictor of grades earned in the class controlling for three additional variables (i.e., grade point average, mathematics background and previous experience in the course). These results could be used to support the creation of an honors section(s) of accounting which could include a more rigorous curriculum taught with real life cases. Previous research supported the concept of an honors program from students, faculty and potential employers. In addition, the results suggest requiring a minimum grade point average and the completion of mathematics requirement before taking introductory accounting.
Keywords: dept.acc; peer-reviewed

Local Government Sustainable Development: A Theoretical Paradigm or a Plan for Action? - Phillips, Janet F.; Strickland, Pamela (Journal of Accounting, Ethics and Public Policy, 2015)
Local governments are a vital component in the national effort to promote sensible methods for community development, growth and social justice. The benefits and challenges of sustainable development have become apparent as more local governments initiate programs to address economic, environmental and social equity issues. This research investigates county and municipal government efforts toward sustainable development using survey information for local governments in the southern United States. Survey responses were analyzed to examine whether local governments “practice what they preach” in terms of actually implementing the sustainable policies proclaimed to be important to their operations. Overall, results suggest local governments do place these policies into action for environmental and social justice issues. In addition, the analysis explores the impact of population size, geographic area and form of government on sustainable development. Measuring the implementation of sustainable policies in terms of dollars, however, proves difficult because there is no consistency among municipalities with regard to reporting the amount of dollars (federal or local) spent in support of sustainability efforts.
Keywords: dept.acc; economic development; environmental protection; local government; peer-reviewed; social equity; sustainability